A recipe for digital ecosystem health - Balancing effectiveness, resilience and profitability - Volz, Felix; Münch, Christopher (European Academy of Management (EURAM) 2024 Conference, 2024)
As digital technologies proliferate, firms navigate complex digital ecosystems to create value, necessitating strategic adjustments and resource allocation. Conflicting approaches, such as hierarchically controlled ecosystems, in contrast to federated data spaces, force companies to strategically assess the plethora of digital ecosystems to adjust their strategies and allocate resources accordingly. However, literature lacks a comprehensive framework for assessing the health of these ecosystems, a gap this study addresses. Through qualitative analysis of 18 semi-structured expert interviews, we delve into the critical factors that underpin the health of digital ecosystems. Our analysis distills these insights into 128 first-order codes, further synthesized into 21 second-order themes. These themes inform the construction of eight pivotal dimensions, organized around three fundamental pillars of digital ecosystem health: effectiveness, resilience, and profitability. Effectiveness emphasizes the ecosystem's operational continuity, driven by factors such as adoption rates, standardization efforts, and the fulfillment of value propositions. Resilience underscores the ecosystem's ability to withstand disruptions, anchored by a collective identity, equitable power dynamics, and organizational agility. Profitability, the cornerstone of competitive advantage, is predicated on transparent benefit distribution and rigorous value assessments. This study not only advances the theoretical understanding of digital ecosystem strategy but also offers actionable insights for managers, aiding their strategic decision-making in digital ecosystem engagemen